2021
DOI: 10.1002/adma.202008298
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Nitriding of Titanium Alloy with Fine Grains at Room Temperature

Abstract: Ti-6Al-4V substrate because of the impact of the particles. Thus, we found that the proposed process could form a nitrided layer on Ti alloys in air at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
(35 reference statements)
0
5
0
3
Order By: Relevance
“…The raw material used in the current study was a CP titanium powder (25.6 µm particle diameter) with 0.122% O, 0.008% N, 0.005% H, 0.037% Fe, and 0.003% C (on a mass basis), with the remainder consisting of Ti. 31) Figure 1 illustrates the process used to form the CP titanium, which had a heterogeneous nitrogen diffusion phase, and two types of specimens fabricated by gas nitriding and spark plasma sintering (SPS). Gas nitriding was conducted at 823 K or 873 K for 18 ks to produce a nitrided layer on the CP titanium powder particle surfaces (see Figs.…”
Section: Materials and Specimensmentioning
confidence: 99%
“…The raw material used in the current study was a CP titanium powder (25.6 µm particle diameter) with 0.122% O, 0.008% N, 0.005% H, 0.037% Fe, and 0.003% C (on a mass basis), with the remainder consisting of Ti. 31) Figure 1 illustrates the process used to form the CP titanium, which had a heterogeneous nitrogen diffusion phase, and two types of specimens fabricated by gas nitriding and spark plasma sintering (SPS). Gas nitriding was conducted at 823 K or 873 K for 18 ks to produce a nitrided layer on the CP titanium powder particle surfaces (see Figs.…”
Section: Materials and Specimensmentioning
confidence: 99%
“…Surface nitriding is an effective method to improve the tribological properties and corrosion resistance of Ti alloys due to the fact that nitrided layers exhibit high hardness, good thermal and chemical stability, and high wear resistance [15,16]. In the field of biomaterials, researchers have found that nitrided layers intrinsically or deliberately formed on the surface of biomaterials showed antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium would easily react with oxygen in the air and then form loose and porous TiO 2 , which could exacerbate the oxidation of the alloy. Therefore, researchers have used various surface treatment techniques, including electroplating [ 4 ], chemical heat treatment [ 5 , 6 , 7 ], ion implantation [ 8 , 9 ], mechanical surface enhancement technology [ 10 , 11 ], and vapor deposition [ 12 , 13 ], to improve the properties of the surface to meet the application requirements.…”
Section: Introductionmentioning
confidence: 99%